The energy sources of CME acceleration - Allawi, H.; Pohjolainen, S. (Advances in Astronomy and Space Physics, 2012)
We investigate the possibility that during the fast acceleration phase of a coronal mass ejection (CME), a freely propagating shock wave could be launched. We test this hypothesis by calculating the speeds of blast waves by using the Taylor-Sedov equation in changing density solar atmosphere, and compare these speeds with the radio type II burst speeds during the CME event on 17 February 2000. The matching speeds and the realistic value of the blast wave energy, 10²⁴ J, lead us to suggest that the CME acceleration phase may involve shocks separating from the initial CME driver.